Routine monitoring of visual outcome of cataract surgery. Part 1: Development of an instrument. Issue 1 (21st December 2004) - Limburg, H; Foster, A; Gilbert, C; Johnson, G J; Kyndt, M
Abstract : Aim: To develop a system for routine monitoring of visual outcome after cataract surgery. Methods: Staff from eight eye centres in Asia and Africa defined the data collection form and report formats to be used for monitoring visual outcome after cataract surgery. Several operational research questions were raised and methods developed to address them. The system was field tested for 6 months and the operational studies undertaken. The system was finalised based upon the experience gained. Findings: Two different systems for data collection were developed: a manual paper tally system and a computer system (cataract surgery record forms (CSRF)). Both systems report on operative complications; the proportion with good outcome (can see 6/18) and poor outcome (cannot see 6/60); and causes of poor outcome. Data are collected at discharge and at specified time intervals at follow up. Both systems were well accepted. Conclusion: The major problem in field testing was data entry errors in centres using the computerised system. Routine monitoring of cataract outcome should be used by individual surgeons or centres to follow trends in their own results over time, and not to compare surgeons, in an atmosphere of trust and support. Visual acuity at discharge, which can readily be collected on all patients, can be used providing it is appreciated that the final results will be much better. Rapid feedback of results can enhance the consciousness of the eye surgeons to causes of poor outcome. Accuracy in data entry and an efficient flow of record forms are essential.